Development of a Global Rating Scale for Inflammatory Bowel Disease. Issue 1 (11th June 2019) - Bitton, Alain; Devitt, Katharine S; Bressler, Brian; Heatherington, Joan; Jairath, Vipul; Jones, Jennifer; Moayyedi, Paul; Weizman, Adam V; Dubé, Catherine; MacIntosh, Donald; Nguyen, Geoffrey C
Abstract: Background: The Global Rating Scale (GRS) is a web-based self-assessment quality improvement tool used to identify gaps in health care, change the focus to patient-centred care and standardize care. There are four levels of achievement ranging from basic-(D) to excellent-(A) service delivery. The goal was to develop a GRS for inflammatory bowel disease (IBD) to improve the quality of care for patients on a system level. Methods: The IBD GRS was developed through an iterative process and modeled upon the successful endoscopy GRS programs in the United Kingdom and Canada. Dimensions, items and statements were drafted based on expert opinions, patient-informed quality indicators and best available evidence, then reviewed and modified by a core committee. A working group of IBD and GRS experts voted in-person to establish consensus on the inclusion and quality of statements. Results: Two dimensions (Clinical Quality and Quality of Patient Experience), 10 items and 89 statements made up the IBD GRS. There was a 100% response rate for each of the 40 votes for statements in the IBD GRS. All statements within each level received a mean rating score between four (agree) and five (strongly agree). Revisions agreed upon during the voting process were incorporated into the IBD GRS. Group consensus was achieved on the inclusion of statements, and 10 items were selected as standards within the two dimensions. Conclusions: We have developed the first IBD GRS with the aim of improving quality of care through ongoing evaluations and improvements by health care teams, focusing on patient-centred care.